Translation Strategies of the Terminologies in the Thesis Abstracts of the Faculty of Industrial Technology - Alexander Yanuar Richardo (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study examines the translation strategies of the terminologies in the eighty thesis abstracts of the Faculty of Industrial Technology. There are twenty abstracts from the Industrial Engineering Department, twenty-one abstracts from the Mechanical Engineering and Design, twenty abstracts from the Business Information System, and nineteen abstracts from the Electrical Engineering Department. The writer uses Baker’s (2018) eight translation strategies as theory. This study applies a descriptive qualitative methodology for the research. The result shows that five of eight translation strategies were used in translating terminologies in the thesis abstracts. The strategies are general word, cultural substitution, loan word/ loan word with explanation, paraphrase using related word, paraphrase using unrelated word. This study shows that loan word is the strategy that is used the most in translating terminologies. This strategy is used because a lot of terminologies from the abstracts of the faculty of Industrial Technology comes from English words.